Base of the skull morphology and Class III malocclusion in patients with unilateral cleft lip and palate - Mariana Maciel Tinano; Milene Aparecida Torres Saar Martins; Cristiane Baccin Bendo; Ênio Mazzieiro (Dental Press Editora, 2015)
OBJECTIVE: The aim of the present study was to determine the morphological differences in the base of the skull of individuals with cleft lip and palate and Class III malocclusion in comparison to control groups with Class I and Class III malocclusion. METHODS: A total of 89 individuals (males and females) aged between 5 and 27 years old (Class I, n = 32; Class III, n = 29; and Class III individuals with unilateral cleft lip and palate, n = 28) attending PUC-MG Dental Center and Cleft Lip/Palate Care Center of Baleia Hospital and PUC-MG (CENTRARE) were selected. Linear and angular measurements of the base of the skull, maxilla and mandible were performed and assessed by a single calibrated examiner by means of cephalometric radiographs. Statistical analysis involved ANCOVA and Bonferroni correction. RESULTS: No significant differences with regard to the base of the skull were found between the control group (Class I) and individuals with cleft lip and palate (P > 0.017). The cleft lip/palate group differed from the Class III group only with regard to CI.Sp.Ba (P = 0.015). Individuals with cleft lip and palate had a significantly shorter maxillary length (Co-A) in comparison to the control group (P < 0.001). No significant differences were found in the mandible (Co-Gn) of the control group and individuals with cleft lip and palate (P = 1.000). CONCLUSION: The present findings suggest that there are no significant differences in the base of the skull of individuals Class I or Class III and individuals with cleft lip and palate and Class III malocclusion.